Search for Supersymmetry in Events with Large Missing Transverse Momentum, Jets, and at Least One Tau Lepton in 7 TeV Proton-Proton Collision Data with the ATLAS Detector - Alonso, Francisco (2012)
A search for supersymmetry (SUSY) in events with large missing transverse momentum, jets, and at least one hadronically decaying τ lepton, with zero or one additional light lepton (e/μ), has been performed using 4.7 fb−1 of proton-proton collision data at √s = 7 TeV recorded with the ATLAS detector at the Large Hadron Collider. No excess above the Standard Model background expectation is observed and a 95 % confidence level visible cross-section upper limit for new phenomena is set. In the framework of gauge-mediated SUSY-breaking models, lower limits on the mass scale Λ are set at 54 TeV in the regions where the τ˜1 is the next-to-lightest SUSY particle (tanβ > 20). These limits provide the most stringent tests to date of GMSB models in a large part of the parameter space considered.